2015
DOI: 10.1063/1.4926482
|View full text |Cite
|
Sign up to set email alerts
|

An origin of good electrical conduction in La4BaCu5O13+δ

Abstract: We have prepared a set of polycrystalline samples of the metallic copper oxide La 4 BaCu 5Àx Co x O 13þd (0 x 0.35) and have measured the resistivity from 4 to 800 K. All the resistivities show metallic temperature dependence with a small magnitude less than 2 mX cm at 800 K, indicating that the metallic conduction is robust against impurities. The robust metallic conduction further suggests that this class of oxide is a promising candidate for electrical leads at high temperature, which might replace platinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Hence, the magnitude of α is determined by the balance between the conductivity and the Seebeck coefficient of each carrier. As Mori et al have pointed out that electrons are majority carriers, which is consistent with the negative Hall resistivity, they dominate the Hall measurement carrier density in LBCO [12]. On the other hand, considering that the fraction of the α e is as small as 4 µV/K at room temperature [10], the large positive Seebeck coefficient of the LBCO can be regarded as the contribution or concentration of holes.…”
Section: Change Of Seebeck Coefficient and Discussion On The Two Charge Carriers' Modelsupporting
confidence: 54%
See 2 more Smart Citations
“…Hence, the magnitude of α is determined by the balance between the conductivity and the Seebeck coefficient of each carrier. As Mori et al have pointed out that electrons are majority carriers, which is consistent with the negative Hall resistivity, they dominate the Hall measurement carrier density in LBCO [12]. On the other hand, considering that the fraction of the α e is as small as 4 µV/K at room temperature [10], the large positive Seebeck coefficient of the LBCO can be regarded as the contribution or concentration of holes.…”
Section: Change Of Seebeck Coefficient and Discussion On The Two Charge Carriers' Modelsupporting
confidence: 54%
“…However, there is no clear evidence of grain orientation, despite the lattice parameters of (121) for LBCO and (101) for SrTiO 3 being identical, which suggests that the grains of the deposited film were rather randomly oriented. The invariance of the c-axis length with Co-substitution has been reported in bulk [12]. No peak for Co 3 O 4 (PDF no.…”
Section: Xrd and Surface Structure Of Lbco Films After The Thermal Annealingmentioning
confidence: 53%
See 1 more Smart Citation
“…However, in the case of La 4 BaCu 5 O 13+δ , we cannot make use of these two experimental results because it is reported that the electrical carrier of this material is composed of both holes and electrons. 26) In the two-carrier model, the thermopower S is described by…”
Section: Resultsmentioning
confidence: 99%
“…The invariance of the c-axis length with Co-substitution has been reported in bulk. 26) The thickness of all films was about 150 nm.…”
Section: Methodsmentioning
confidence: 99%